Serum level of soluble tumor necrosis factor receptor 2 is associated with the outcome of patients with diffuse large B‐cell lymphoma treated with the R‐CHOP regimen. (7th July 2013) - Nakamura, Nobuhiko; Goto, Naoe; Tsurumi, Hisashi; Takemura, Masao; Kanemura, Nobuhiro; Kasahara, Senji; Hara, Takeshi; Yasuda, Ichiro; Shimizu, Masahito; Sawada, Michio; Yamada, Toshiki; Seishima, Mitsuru; et al.
Abstract: Background: Serum soluble tumor necrosis factor receptor 2 (sTNFR2) concentration predicted the clinical outcome of patients with aggressive non‐Hodgkin's lymphoma including diffuse large B‐cell lymphoma (DLBCL) treated with CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisolone) in our previous study. However, after rituximab (R) was introduced in clinical practice, R‐CHOP replaced CHOP as the standard therapy for DLBCL. Patients and methods: In this study, we re‐evaluated the prognostic significance of serum sTNFR2 in 154 patients with DLBCL treated with R‐CHOP. Results: Five‐yr overall survival (5‐yr OS) rates with sTNFR2 ≥20 ng/mL and <20 ng/mL were 29.2% and 83.3% ( P  < 0.0001), respectively, and the corresponding 5‐yr progression‐free survival (5‐yr PFS) rates were 26.9% and 76.4% ( P  < 0.0001), respectively. A multivariate analysis revealed that serum sTNFR2 and complete remission (CR) were independent prognostic factors for both OS (CR: P  < 0.0001, sTNFR2: P  = 0.0001) and PFS (CR: P  < 0.0001, sTNFR2: P  = 0.0001). The prognosis of patients with poor risk groups according to the revised International Prognostic Index who also had high serum sTNFR2 was especially poor. Conclusion: Serum sTNFR2 might be a powerful prognostic factor for patients with DLBCL in the rituximab era.